Estudo da estrutura populacional, caracterização molecular de Aniba rosaeodora (Ducke) pau-rosa em áreas de distribuição potencial do distrito de Masisea, Ucayali, Peru. - Revilla, Jorge Chávez [UNESP] (2024)
Aniba rosaeodora Ducke, known as "rosewood", is one of the most valuable tree species in the Amazon, famous for its linalool-rich essential oil, used in the cosmetics industry. However, their overexploitation has led to the decrease of their natural populations, affecting their production and genetic diversity, putting the species at risk of extinction. The species is found mainly in forests in Brazil, Colombia, Ecuador, Peru and other countries in the Amazon region, growing in habitats of plateaus and streams, and can reach up to 30 m in height. Seed dispersal depends on animals such as parrots and toucans, but their natural regeneration is threatened by predation and other factors. This study seeks to better understand the patterns of dispersion, density and population dynamics of A. rosaeodora in the Peruvian Amazon, in order to propose strategies for its conservation and forest management. Population dynamics play a key role in the conservation and domestication of species. From genetic assays of forest species in the Peruvian Amazon, methodologies were developed to evaluate the phenotypic variation of their traits of commercial interest. These methodologies were applied in conservation and domestication studies, through stability, adaptability and productivity tests of progenies of Guazuma crinita Mart, in addition to the qualitative and quantitative control of phenotypes of Calycophyllum spruceanum Benth. These studies, carried out in the Aguaytía river basin in the Peruvian Amazon, can be adapted for methodological application in Aniba rosaeodora Ducke in the region, with the aim of promoting its conservation and sustainable management.